Inhibition of macrophage polarization and pyroptosis in collagen-induced arthritis through MSC-exo and ginsenoside Rh2 - Zhongsheng Zhou; Shuhui Wu; Yang Li; Pu Shao; Jinlan Jiang (Arthritis Research & Therapy)
Abstract Background Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by joint inflammation, tissue damage, and fibrosis, significantly affecting the quality of life. While there are currently some effective treatments available, they often come with side effects. There is an urgent need to find new treatments that can further improve therapeutic outcomes and reduce side effects. Methods Our study investigates the role of Mesenchymal Stem Cell exosomes (MSC-exo) combined with Ginsenoside Rh2 (Rh2) in the treatment of RA. We specifically focus on how this combined strategy influences macrophage polarization and pyroptosis. This research utilized a collagen-induced rat arthritis model. Results The study findings reveal that the combination of MSC-exo combined with Rh2 can inhibit the polarization of M1 macrophages, increase the proportion of M2-like macrophages, and suppress M1-like macrophage pyroptosis via the NLRP3/Caspase11/GSDMD-N pathway. In the rat arthritis model, the combination of MSC-exo and Rh2 showed synergistic therapeutic effects. Conclusion This research contributes to a deeper understanding of RA’s pathogenesis and presents new potential targeted therapeutic interventions. The combined application of MSC-exo and Rh2 offers promising insights for future innovative strategies in RA treatment, paving the way for more effective management of this autoimmune disease.